Contemporary Outcomes in Low‐Gradient Aortic Stenosis Patients Who Underwent Dobutamine Stress Echocardiography. Issue 6 (19th March 2019) - Sato, Kimi; Sankaramangalam, Kesavan; Kandregula, Krishna; Bullen, Jennifer A.; Kapadia, Samir R.; Krishnaswamy, Amar; Mick, Stephanie; Rodriguez, L. Leonardo; Grimm, Richard A.; Menon, Venu; Desai, Milind Y.; Svensson, Lars G.; et al.
Abstract : Background: Detection of flow reserve (FR) by dobutamine stress echocardiography is used for risk stratification in low‐gradient aortic stenosis (AS). Prognostic significance of dobutamine stress echocardiography in the transcatheter aortic valve replacement era is unclear. We aimed to assess the current relevance of FR. Methods and Results: We studied 235 patients with low‐gradient severe AS (rest aortic valve area ≤1.0 cm 2 or indexed aortic valve area ≤0.60 cm 2 /m 2 ; mean aortic valve gradient <40 mm Hg) and left ventricular ejection fraction <50%) with dobutamine stress echocardiography done September 2010 through July 2016. FR was defined by ≥20% stroke volume increase. We diagnosed "true‐severe AS" if peak aortic valve velocity ≥4 m/s occurred with aortic valve area ≤1.0 cm 2 (or indexed aortic valve area ≤0.6 cm 2 /m 2 ). At a median time of 51 days, 128 patients underwent aortic valve replacement, either surgical aortic valve replacement (n=42) or transcatheter aortic valve replacement (n=86). FR was observed in 138 patients, while 86 patients had true‐severe AS. During median follow‐up of 2.3 years, 138 patients died. In a multivariable model, aortic valve replacement (hazard ratio 0.41, 95% CI: 0.29–0.58, P <0.001) and lower Society of Thoracic Surgeons score (hazard ratio 1.06, 95% CI: 1.04–1.09, P <0.001) were associated with better survival, while FR was not predictive. aortic valve replacement was associated with survival regardless of the presence or absence of FR or AS severity stratification. Conclusions: In low‐gradient AS with reduced ejection fraction, FR or AS severity stratification by dobutamine stress echocardiography was not associated with survival. Aortic valve replacement was associated with better survival in low‐gradient AS independent of FR. Abstract : See Editorial by Annabi et al